PERANCANGAN APLIKASI KAMUS BAHASA JAWA-INDONESIA BERBASIS ANDROID - Risa Wati; Siti Ernawati (Jurnal Techno Nusa Mandiri, 2018)
Indonesia is a country that has many regional languages. The use of local languages has been abandoned by many people. As good citizens ofIndonesia we must preserve the local languages that are owned, one of which is Javanese. In making it easier to learn Javanese, we need a translator application or what is often called a dictionary. In designing this translator application, researchers use the waterfall model which consists of four steps. Design of this application uses eclipse software. This application is applied to mobile devices, especially mobile phones that have an Android operating system. The purpose of this application is to make it easier for users to translate Javanese into Indonesian and Indonesian into Javanese, so that the application has an optimal function.